A Comparative Study of Pulmonary Function Tests in Air Conditioner Users and Non Users - Begum, Sharmin Ara; Kuryshi, Mohammad Syedul Alam; Begum, Momtaz; Akhter, Shahin; Rahman, Mir Mahbubur (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: One of the components of the modern life style is the intensive use of air conditioner for thermal comfort. With modernization, use of electric machines along with AC is rising day by day. Increased inhalation of cold dry air of air conditioner ultimately may cause alteration of pulmonary functions. The objective of this study was to assess the effect of air conditioner on pulmonary function tests. Materials and methods: This quasi experimental study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram, during January 2019 to December 2019 in collaboration with Continental Group Private Limited (Abu Baqar Ciddique) Chattogram and EPV (Energypac Power Venture) Chittagong Limited, Patiya, Chattogram. 35 apparently healthy adult males between the ages 20-45 years, working in air conditioned environment were taken as case. 35 healthy age and sex matched subjects, working in non air conditioned environment were taken as control. This study was done to measure pulmonary function test parameters among healthy Air Conditioner (AC) users and they were compared with non users of AC to see the effects of Air Conditioner (AC) on lung functions. Lung function test parameters like PEFR, MMF, FEF 25% , FEF and FEF , were measured by digital spirometer. Unpaired Student’s t test and Chi-square test were done by using SPSS-25 for statistical analysis. Results: The mean value of PEFR, MMF, FEF 75% and FEF were significantly (p<0.05) lowered in AC users comparing with control. The mean value of FEF 50% were (p>0.05) lowered in AC users comparing with control. Conclusion: The result of this study suggest that pulmonary function is significantly decreased after usage of air conditioner. Therfore public awareness for proper maintenance of AC, periodic analysis of pulmonary functions, limited use of AC and regular respiratory exercise can be recommended for preserving respiratory efficiency. JCMCTA 2025 ; 36 (2) : 112-117